Kedudukan Perjanjian Damai dalam Penyelesaian Perkara Perdata - Redha Rizky (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Peace agreements play an important role in civil dispute resolution in Indonesia. As a faster, cheaper, and more conciliatory alternative to litigation, amicable agreements are recognized by law through the Civil Code (KUHPerdata) and several other regulations. This research aims to examine the position of peace agreements in the Indonesian civil law system, as well as their legal implications in the context of litigation and alternative dispute resolution. The research method used is normative legal research with secondary data analysis. The results show that a peace agreement has the same legal force as a court decision and can be legally executed. However, peace agreements have limitations in some cases concerning the legal status of a person or the public interest. This research is expected to provide further understanding of the importance of amicable agreements as an effective solution in resolving civil disputes.